Effect of austempering temperature on microstructure and mechanical properties of unalloyed ductile iron - Bošnjak, Branka (Kovine zlitine tehnologije, 1999)
Austempered ductile cast iron (ADI) has emerged in the last several decades as a major engeneering material. The heat-treating of the ductile cast iron produces austempered ductile iron (ADI) with an excellent combination of strength, fracture toughness and wear resistance for a wide variety of applications in automotive, rail and heavy engineering industries. The austempering temperature is the most important parameter in determining both the structure and the mechanical properties of unalloyed austempered ductile irons. It is varied in the range of 250-450°C. The aim of this work was to optimize the microstructure, and consequently the properties of ductile cast iron of composition Fe-3.48C-2.7Si (in wt.%). The analysis of the microstructure was performed by light microscopy. scanning electron microscopy, and X-ray diffraction.
Keywords: siva litina; mehanske lastnosti; mikrostruktura